Integration of Chitosan and Ageratum conyzoides Extract in Hydrogel Patches for Enhanced Wound Closure Kinetics under the TIME Framework - Prihantini, Malinda; Anas, Yance; Heroweti, Junvidya; Mulangsri, Dewi Andini Kunti; Jamaludin, Wahyudin Bin; Nahla, Luthfia Mufaridhotun; Mahadika, Reyhan Raka; Hawa, Fazdilatul; Azkya, Nayla; Fassadila, Rifka Sephia (Borneo Journal of Pharmacy, 2026)
Chronic wounds pose a significant healthcare challenge in Southeast Asia, with prevalence rates reaching 50.8%. Conventional systemic therapies often fail due to persistent inflammation and bacterial biofilm formation. This study presents a novel approach that combines chitosan, a hydrophilic scaffold that maintains optimal moisture and prevents microbial contamination, with Ageratum conyzoides, which is rich in flavonoids with anti-inflammatory and pro-proliferative properties. This study aimed to evaluate the impact of chitosan combined with A. conyzoides in a hydrogel patch formulation on wound healing as a comprehensive approach to the TIME (Tissue, Inflammation, Moisture, Epithelization) concept. The standardized plant material was formulated into patches by a solvent‐casting method using three extract‐to‐chitosan ratios: F1 (2:0), F2 (1:1), and F3 (2:1). Evaluation encompassed physical characterization, acute dermal irritation, and wound‐healing activity assessment. Plant material met the Indonesian Herbal Pharmacopeia standards, yielding 9.96 ± 0.10% total flavonoid content, with phytochemical screening confirming flavonoids, phenolics, and quinones. All formulations demonstrated favorable physical characteristics: thickness of 0.08–0.11 mm, folding endurance of 64–479 folds, and moisture absorption of 6.12–9.39%, with no acute dermal irritation observed in rabbits. In a 14-day linear incision wound model using male Wistar rats, F3 achieved superior healing efficacy (97% closure, rate constant 0.2972 day⁻¹), reaching 90% closure by day 7.75, significantly outperforming the positive control (Bioplacenton®, 89%) and negative control (79%). These results highlight F3’s synergistic effects via anti-inflammatory and proliferative mechanisms, following first-order kinetics and comprehensively addressing the TIME framework to enhance wound healing.